(3QSGdI GdhLhO hJMbjb eQGJH GdhLhOs - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s ((3eMeO bdj Hf ejQRG GdNhFjfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3ajbhd GdYHO GdeScjf(B: (3CMeO Hf Rjf GdOjf GdCMSGFj(B... (3Cf GdhLhOGJ GdJj jTGQ HdaX GdhLhO(B...s
(3BNQgG (B:s
(3JYhOhf dCLd GdJfYe HGdfYje GdCHOj (B... (3dG jUd Edi GdSeGA EdG ef fRd efgG(B. (3gPG BNQ eG ChQOJgG(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs